New species of the leafhopper tribes Agalliini and Macropsini (Hemiptera: Cicadellidae) from north and northeast India with checklist of species of the tribes from the Indian subcontinent - Viraktamath, C.a.; Yeshwanth, H. M.; Ajaykumara, K.m. (Zootaxa, 2024)
One new species of Agalliini, Nandigallia serratistyla sp. nov. and one new species of Macropsini, Oncopisis (Parasitades) ramanii sp. nov. from Arunachal Pradesh, India are described and illustrated. New locality records for Durgades nigropicta Distant, Igerna priyankae Viraktamath, I. shillongensis Meshram, I. wilsoni Viraktamath and Varicopsella elegans Viraktamath are given and most of these species are illustrated. A revised key to species of Nandigallia Viraktamath is provided. In addition, checklists of genera and species of the tribes Agalliini and Macropsini recorded from the Indian subcontinent are also provided.